2021
DOI: 10.1111/ced.14870
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histopathological features of adult patients with dermatomyositis and melanoma differentiation associated‐5 autoantibody seropositivity status, as determined by commercially available testing: a retrospective, single‐institution comparative cohort study

Abstract: Background. Although melanoma differentiation associated (MDA)-5 autoantibodies have been widely explored in dermatomyositis (DM), most studies have relied on MDA-5 autoantibody testing performed in research settings, rather than the nowavailable commercial laboratory tests. Aim. To characterize the clinical and histopathological data in patients with DM and circulating MDA-5 autoantibodies, as defined by commercially available testing. Methods. This was a retrospective review of patients with DM who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 18 publications
(59 reference statements)
0
13
1
7
Order By: Relevance
“…However, unlike previous publications, we could not establish a relationship with panniculitis, periungual involvement 12 or calcinosis, 13 but we could confirm that the presence of Raynaud's disease is rare 5 . Interestingly, other authors found a highly significant increased frequency of Raynaud's disease in association with anti‐MDA5 seropositivity, not emphasized in the literature to date 9 …”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…However, unlike previous publications, we could not establish a relationship with panniculitis, periungual involvement 12 or calcinosis, 13 but we could confirm that the presence of Raynaud's disease is rare 5 . Interestingly, other authors found a highly significant increased frequency of Raynaud's disease in association with anti‐MDA5 seropositivity, not emphasized in the literature to date 9 …”
Section: Discussioncontrasting
confidence: 96%
“…There are few studies involving anti‐MDA5 + patients, our study being the one with the highest number of total cases. Other than the present study, only one was a multicenter study 9,11–14 …”
Section: Discussionmentioning
confidence: 87%
“…Several pieces of evidence point toward a central role of vascular injury in the pathogenesis of anti-MDA5 DM: (i) Patients frequently show typical cutaneous features such as skin ulcers due to severe vasculopathy; (ii) Histopathology of palmar papules, as well as lung tissues highlights vasculopathy ( 12 , 15 , 105 ); (iii) Biomarkers of endothelial dysfunctions have been identified in the sera of patients ( 106 , 107 ); (iv) Patients exhibited a strong IFN-I signature distributed in the vasculature of the skin ( 108 , 109 ). It is important to emphasize that these particular features are observed in the skin and the lungs of patients with anti-MDA5 DM but that there is no or few signs of vasculopathy nor of an enhanced IFN-I signature, compared to other DM, in muscle tissue of anti-MDA5 DM patients ( 21 , 22 ).…”
Section: Pathogenesis Of the Diseasementioning
confidence: 99%
“…6 Patients with MDA5-associated dermatomyositis may have typical cutaneous findings of dermatomyositis but characteristically have a distinctive phenotype that includes cutaneous and oral ulcerations and painful palmar papules; nonscarring alopecia, calcinosis, arthritis, and mechanic's hands have also been associated with this antibody. 6,7 In contrast to most patients with dermatomyositis, those with MDA5-associated dermatomyositis often do not experience proximal muscle weakness and may have normal creatine kinase and aldolase levels on blood testing. 6 In addition, MDA5-associated dermatomyositis is associated with an elevated risk of interstitial lung disease (ILD), with a reported prevalence ranging from 5% to 65%.…”
Section: Discussionmentioning
confidence: 99%